A bidirectional converter with integrated voltage equalizer for series‐connected supercapacitors. (9th January 2022) - Yang, Xiaoguang; Jia, Zhe; Wang, Dexin; Zhao, Xiaobing; Su, Yukui; Nie, Baoxin
Summary: Energy storage systems include not only a charge/discharge bidirectional converter but also a separate voltage equalizer. This paper proposes a bidirectional converter with an integrated voltage equalizer, which saves a DC–AC converter, thus significantly reducing the size, cost, and complexity of the equalization circuit. In addition, integrating the equalizer into the bidirectional converter also has a positive impact on the realization of ZVS operation. Analytical models have been established that can be used for accurate prediction, optimal design, and effective control of the proposed converter. A control strategy is proposed, which not only enables the cells to be automatically balanced when the cell string is charged/discharged but also enables ZVS operation within a wide range of voltage changes and minimizes the RMS value of the primary current. An experimental prototype of 60 W applied to nine supercapacitors (SCs) in series was built, and the experimental results verified the theoretical analysis and demonstrated the characteristics of the proposed converter. Abstract : This paper proposes a bidirectional converter with an integrated voltage equalizer to simplify the system. The proposed integrated converter saves a DC–AC converter, which is necessary for conventional string‐to‐cell equalizers. Integrating the equalizer into the bidirectional converter also has a positive impact on the realization of ZVS operation. The proposed converter can automatically balance the cells while charging/discharging the string over a wide output voltage range.